Assessment of impacts of utilization on water resources in the basin of trans-boundary Red river system - Cuong, Do Huy; Dan, Nguyen Lap; Anh, Bui Thi Bao; Nhan, Nguyen Thi; Tung, Nguyen Xuan; Hung, Pham Duc; Linh, Nguyen Thuy (Vietnam Journal of Marine Science and Technology, 2020)
The Red river system is the large trans-boundary river system, there has been no united system of hydrology stations as well as integrated plan for the water use and management in the whole basin. The trend of water resources change in the Red river system basin has been assessed on the basic of statistic analyses of data observed during the studies, especially in the time when the exploitation of water resources has been intensified for the multisectoral development. This paper shows some of the results from considerations of the water use in the highlands that is influential in water resources in the Red river system basin and the planned reservoirs which are built in the basin of Red river system. The results include the assessment of the state and trend of water resources in the Red river system basin, the trend of water level lowering in the lowlands and its impacts.